Updates on animal models of systemic sclerosis. Issue 3 (September 2016) - Soare, Alina; Ramming, Andreas; Avouac, Jerome; Distler, Jörg H.W.
Systemic sclerosis (SSc) is a connective tissue disease of unknown etiology that is characterized by fibrosis of the skin and several internal organs, vasculopathy, inflammation and autoimmunity. Animal models have improved our understanding of the pathogenesis of SSc. Many inducible and genetic animal models of SSc have been developed and characterized in the last years. All of these models have different strengths and limitations and mimic different aspects of the pathogenesis of SSc. The purpose of this review is to summarize the characteristics of the various animal models of SSc and to provide an outline of how to use these models to study certain aspects in the pathogenesis of SSc and to test the effects of potential therapeutic approaches.